What is the essence of pleasure and its status in Islamic ethics according to professor Misbah Yazdi’s viewpoint? - roohollah shahryary (اخلاق وحیانی)
This study is going to analyze the issue of pleasure using descriptive analysis method and referring to professors Misbah Yazdi’s ideas.The main question to answer is: What is the status of pleasure in Islamic ethics? The results of the survey shows that the pleasure is a main inborn inclination and it means every kinds of perception about everything which is pleasurable for human’s self will. Perception of pleasure has four conditions: one’s suitable ability to perceive pleasure, it should be agreeable to self, there should be the conditions of pleasure perception, the issue should be in the era of one’s awareness and attention. This study also shows that the pleasure is the main motivation in optional behaviors as there is no optional behavior which the agent is going to do without absorption and agreement of that action with his self. The pleasure according to its role in the ultimate happiness of human being is divided to praiseworthy and contemptable ones.To know the noble pleasure Professor Misbah evaluated the pleasure according to Quranic logic via two measures: Quality and continuity. Furthermore to know the noble pleasure it is necessary to know the real happiness of human being so recognition of real happiness necessitate the recognition of noble pleasures and vice versa, recognition of noble pleasures necessitate the recognition of real happiness. In his view the elements which determine the preference of a pleasure or recognition of its instance are not always optional. Generally these are: natural needs, habit, reason and revelation